Representation of Female In Arabic: Feminism and Gender Relations Perspective - Novia Wulandari; Aida Hayani (Islah: Journal of Islamic Literature and History, 2020)
When discussing about gender, it matters not only as a grammatical phenomenon, but also as a deeper meaning of the relationship between men and women. As a representation produced by human being containing certain values about an abstracted object, language embodies personal value, social values, cultural values, and political values. The correlation between gender and language in Arabic language has a characteristic since it is also influenced by the religion affected the relationship between men and women. Therefore, the main problems are how women depicted in this language and how their image is compared with man. In order to gain the depiction, feminism is seen as an appropriate tool for analyzing it. This approach is chosen since feminism approach providing general analysis about condition contributed to woman and digging into cultural understanding towards what is meant by being woman. The findings conclude that woman depiction are seen as 1) a branch while man as a root; 2) imperfect person since their thinking are unequal to men.